2021
DOI: 10.1002/mds.28581
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐Spinal Direct Current Stimulation for Managing Primary Orthostatic Tremor

Abstract: A BS TRACT: Background: Primary orthostatic tremor (POT) is a rare disorder, characterized by 13 to 18 Hz tremor in the legs when standing and is often refractory to medical treatment. Epidural spinal cord stimulation has been proposed as an alternative treatment. However, this approach is invasive, which limits its application. Objective: Trans-spinal direct current stimulation (tsDCS) is a non-invasive method to modulate spinal cord circuits. The aim of this proof-of-concept study was to investigate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Although the mechanisms of action of different neuromodulation strategies on spinal circuits are yielding to experimental and computational approaches, we are far from having a sufficient understanding to inform therapeutic decisions. We focused on tsDCS, a non-invasive neuromodulatory tool with the potential for improving motor function after neurological disease and injury ( Rahman et al, 2013 ; Ahmed, 2014 ; Song et al, 2015 , 2016 ; Mekhael et al, 2019 ; Abualait, 2020 ; Lamy et al, 2021 ). We show a novel action on motoneurons using single motor unit recordings; c-tsDCS produces a robust augmentation of spontaneous single motor unit firing that persists after stimulation stops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of action of different neuromodulation strategies on spinal circuits are yielding to experimental and computational approaches, we are far from having a sufficient understanding to inform therapeutic decisions. We focused on tsDCS, a non-invasive neuromodulatory tool with the potential for improving motor function after neurological disease and injury ( Rahman et al, 2013 ; Ahmed, 2014 ; Song et al, 2015 , 2016 ; Mekhael et al, 2019 ; Abualait, 2020 ; Lamy et al, 2021 ). We show a novel action on motoneurons using single motor unit recordings; c-tsDCS produces a robust augmentation of spontaneous single motor unit firing that persists after stimulation stops.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive trans-spinal cord direct current stimulation (tsDCS) has the potential for promoting spinal motor function through its modulatory actions on sensory processing ( Aguilar et al, 2011 ), reflexes ( Winkler et al, 2010 ; Song et al, 2015 ; Mekhael et al, 2019 ), the motor cortex motor map ( Ahmed, 2013a ; Song et al, 2015 ), and enhancing spinal motor circuit function and motor output ( Ahmed, 2011 ; Jankowska, 2017 ; Song and Martin, 2017 ). tsDCS has also been used for treating different neurological diseases and injuries (e.g., Picelli et al, 2015 and Lamy et al, 2021 ) and for pain control ( Guidetti et al, 2021 ). The effects of tsDCS tend to be polarity dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Primary orthostatic tremor (POT) is a rare disorder characterized by 13–18 Hz tremors in the legs when standing and is often refractory to medical treatment. Lamy et al (2021) investigated the potential beneficial effects of trans-spinal direct current stimulation (tsDCS) in POT. Their results showed that cathodal-tsDCS reduced both tremor amplitude and frequency and lowered corticospinal excitability, whereas anodal-tsDCS reduced tremor frequency only.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that cathodal-tsDCS reduced both tremor amplitude and frequency and lowered corticospinal excitability, whereas anodal-tsDCS reduced tremor frequency only. A single session of tsDCS significantly improved POT-induced instability; thus, Lamy et al (2021) hypothesized that tsDCS may induce spinal and supraspinal effects via ascending pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of subjective unsteadiness in OT is not well-understood but has been attributed to a tremulous disruption of the proprioceptive feedback from the lower limbs ( 93 ). It is not clear whether the disruption is altered by trans-spinal direct current stimulation, which has been recently found to provide modest improvement in OT ( 94 ). The term “OT plus” is used to describe a situation when OT co-manifests with additional neurological conditions such as parkinsonism, ataxia, dementia.…”
Section: Overview Of the Axis-i Tremor Syndromesmentioning
confidence: 99%